2011
DOI: 10.1021/ja111055q
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Single-Walled Aluminosilicate Nanotubes from Molecular Precursors and Curved Nanoscale Intermediates

Abstract: We report the identification and elucidation of the mechanistic role of molecular precursors and nanoscale (1-3 nm) intermediates with intrinsic curvature in the formation of single-walled aluminosilicate nanotubes. We characterize the structural and compositional evolution of molecular and nanoscale species over a length scale of 0.1-100 nm by electrospray ionization mass spectrometry, nuclear magnetic resonance spectroscopy ((27)Al liquid-state, (27)Al and (29)Si solid-state MAS), and dynamic light scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
114
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 56 publications
3
114
0
Order By: Relevance
“…The suppression of this mechanism in small volumes indicates that it is likely to be a nucleated process; moreover, the spatial development of the fibrillar phase leads to the depletion of the spherical phase, suggesting that the fibrils grow through monomer addition and that thermodynamic stability of the monomers in the fibrillar phase is greater than in the sphere phase; these observations suggest a thermodynamic driving force for the formation of the intermediate fibrillar phase. Interestingly, examples of transitions from amorphous aggregates into ordered tubular structures have been reported in the field of inorganic polymers 61,62 . While it has not been demonstrated that such systems follow the mechanism that we elucidate here for supramolecular polymer phase transitions, there are similarities in the overall process.…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of this mechanism in small volumes indicates that it is likely to be a nucleated process; moreover, the spatial development of the fibrillar phase leads to the depletion of the spherical phase, suggesting that the fibrils grow through monomer addition and that thermodynamic stability of the monomers in the fibrillar phase is greater than in the sphere phase; these observations suggest a thermodynamic driving force for the formation of the intermediate fibrillar phase. Interestingly, examples of transitions from amorphous aggregates into ordered tubular structures have been reported in the field of inorganic polymers 61,62 . While it has not been demonstrated that such systems follow the mechanism that we elucidate here for supramolecular polymer phase transitions, there are similarities in the overall process.…”
Section: Discussionmentioning
confidence: 99%
“…Single-walled aluminosilicate nanotubes (AlSiNTs) are excellent candidates for fabricating various functional nanohybrid materials due to their well-defined one-dimensional structure (Yucelen et al 2011;Thill et al 2012), vast range of tunable compositions (Avellan et al 2014), functionalizable surfaces (Kang et al 2011), attainability in pure form without a catalyst (Yucelen et al 2011), and ability to readily form hydrogels, transparent films, powders, and coatings (Jiravanichanun et al 2011;Kuroda et al 2012). As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to IR, XRD, TEM, SEM, and AFM, the formation and characterization of imogolite has been studied by techniques such as FTIR spectroscopy, X-ray absorption spectroscopy (XAS), nuclear magnetic resonance (NMR), electrospray ionization mass spectrometry (ESI-MS), and small-angle X-ray scattering (SAXS) 46,47 . However, the experimental conditions of the synthesis and the particular limitations of each characterization technique have hindered the elucidation of the growth mechanism for this aluminosilicate.…”
Section: Introductionmentioning
confidence: 99%
“…Research on structures analogous to imogolite, such as aluminogermanates ((OH) 3 Al 2 O 3 GeOH) have led to significant progress on a proposal for a general mechanism that explains the formation of imogolite 11,46,47 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation